External factors and the Professional Career selection in Law students Arequipa 2011 - Sandro Peralta Arotaype (2019)
The present research "External factors and the professional career selection in law students Arequipa 2011”. Objetive: Determine what external factors are the ones that in the professional career selection, taking into account that nowaday one of the most demanding professional career in law. The variables the research were: External factors of the professional career (variable 1) an the election of the professional career (variable 2). Hypothesis: we started with the Hypothesis that the social cultural, ethical moral and the scientific environment are considered factors by the students of the first professional program. The applied technique was a colective and structured survey and the instrument was a questionary likert scale of 55 affirmations with alternatives of to choose. Conclusions: the external factors of familiar link were (52,2%), and the educational system (58%) they are the ones that have the highest level presence into the professional career of law that were elected by the students who did the survey.